2020
DOI: 10.1111/cod.13475
|View full text |Cite
|
Sign up to set email alerts
|

“Hand‐borne” allergic contact dermatitis of the face to slime, possibly photoaggravated

Abstract: Homemade slime is a popular children's toy, created by mixing several household products. 1 Several cases of contact dermatitis from homemade slime were reported recently. 2 We describe a case of "handborne" contact dermatitis of the face due to homemade slime, which was possibly photoaggravated. CASE REPORTA 13-year-old girl presented with pruriginous lesions on the face which appeared 2 days before consultation. Dermatological examination revealed papules and vesicles involving the cheeks ( Figure 1A) and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…All reports are recent and included seven studies from 2018, five from 2019, and four from 2020 (Tables 1 and 2). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Among them, seven are from the United States, whereas the remaining are from France, Belgium, Brazil, Switzerland, Turkey, Canada, Spain, and Tunisia, published during the period between 2000 and 2021. From the selected 16 studies, 5 reported more than one case of intoxication while the remaining studies reported only a single case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reports are recent and included seven studies from 2018, five from 2019, and four from 2020 (Tables 1 and 2). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Among them, seven are from the United States, whereas the remaining are from France, Belgium, Brazil, Switzerland, Turkey, Canada, Spain, and Tunisia, published during the period between 2000 and 2021. From the selected 16 studies, 5 reported more than one case of intoxication while the remaining studies reported only a single case.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Given that the risks associated with the development of skin reactions and immune responses are very unique between individuals, 32 the severity and clinical evolution of intoxications caused by slime varied from severe cases of difficult management to milder cases 13,14,18,20,23 of good resolution. 15,26,27 It is noteworthy that individuals who have suffered from previous episodes of atopy are more likely to develop atopic dermatitis and present more severe or intense ACD or ICD symptoms. 32,33 Despite this, most studies did not inform the existence of previous episodes of atopy.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2018, there have been 15 case reports or case series on slime dermatitis (Table 1). 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] The literature describes 21 total patients, including 7 (33%) with a history of atopy and 4 (19%) with atopic dermatitis in particular. Of these 21 patients, 18 (86%) were female, and all were aged 7 to 13 years (mean, 10.3 [SD, 1.7] years).…”
Section: Literature Reviewmentioning
confidence: 99%